If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -12 = 9n + -63 Reorder the terms: -12 + 2n = 9n + -63 Reorder the terms: -12 + 2n = -63 + 9n Solving -12 + 2n = -63 + 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. -12 + 2n + -9n = -63 + 9n + -9n Combine like terms: 2n + -9n = -7n -12 + -7n = -63 + 9n + -9n Combine like terms: 9n + -9n = 0 -12 + -7n = -63 + 0 -12 + -7n = -63 Add '12' to each side of the equation. -12 + 12 + -7n = -63 + 12 Combine like terms: -12 + 12 = 0 0 + -7n = -63 + 12 -7n = -63 + 12 Combine like terms: -63 + 12 = -51 -7n = -51 Divide each side by '-7'. n = 7.285714286 Simplifying n = 7.285714286
| 1+2x=2(2x+2)-3(1x-4) | | 12x^2-7x-4=0 | | 2.5*2.25= | | 15/3*2+3-4-3-7 | | (9-3i)-(2+i)= | | -6(7y-2)=31+9y | | 1+2x=2(x+2)-3(1x-4) | | -6=3t-36 | | 4t(6*6)/78t=567 | | 8n+32=2n-8 | | 4t(6*6)/78t= | | -25/24=-2/3-3/2n | | -310=5(7a-6) | | 31+8v=-1+7(3v-1) | | 11-(x/4)=-23 | | 9/4=f/28 | | 1+6a=-11+3a | | 8x+7=8+3x | | 19=-6+8(f-4) | | 265v^2+289=0 | | x-7=13-3x | | 8p-56=9p+10 | | rt-2n=yfort | | 3y(2y+1)+2y(y+6)=25 | | 9x^2-103x+328=0 | | 4x+3=7x-19 | | 3y(2y+1)+2y(y+6)= | | 180=2x-5+4x+10 | | 2+5/x-4 | | 3d-34.56=17.01 | | =3y(2y+1)+2y(y+6) | | 3x+10+5=180 |